2007
DOI: 10.1016/j.ijcard.2006.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Depression in patients with acute myocardial infarction: Influence on autonomic nervous system and prognostic role. Results of a five-year follow-up study

Abstract: Word count: 2754 2 ABSTRACT:Background -Although previous studies demonstrated an association between depressive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
4
37
0
1
Order By: Relevance
“…Studies of similar methodological quality published since the EPC report have shown relations between post-MI depression symptoms and hospital readmission 21,26,29 and nonfatal cardiac events or symptoms. 8,13 Two adequately powered studies 26,29 did not support the relation between depression and nonfatal events.…”
Section: Evidence Question 2: What Is the Prevalence Of Continued Depmentioning
confidence: 99%
“…Studies of similar methodological quality published since the EPC report have shown relations between post-MI depression symptoms and hospital readmission 21,26,29 and nonfatal cardiac events or symptoms. 8,13 Two adequately powered studies 26,29 did not support the relation between depression and nonfatal events.…”
Section: Evidence Question 2: What Is the Prevalence Of Continued Depmentioning
confidence: 99%
“…In our cohort, patients with more symptoms of depression were more likely to lack a steady partner than those with fewer symptoms. Other potential mechanisms suggest a direct role for depression in cardiovascular outcomes via cardiac autonomic dysfunction [40], heart rate variability [41] and inflammatory markers [42].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Affective disorder patients were reported to show rhythm disturbances with lower HRV values [40][41][42], HRValso being mediated by serotonergic receptors [43]. Controlled studies of comorbidity with ischemic heart disease (IHD) revealed reduced HRVand SDNN [44][45][46] in depressed versus non-depressed individuals. It has been Table 1 Proposed risk factors for developing depression in CHF…”
Section: Activation Of Neurohormonal Systemsmentioning
confidence: 99%